ORGANIC AGRICULTURE DEVELOPMENT STRATEGY IN THE KRAYAN HIGHLANDS TO STRENGTHEN SUSTAINABLE FOOD SECURITY FOR BORDER COMMUNITIES - Beny Patisadia (Universitas Negeri Makassar, 2026)
The Krayan Highlands in Nunukan Regency, North Kalimantan, represent an organic farming area grounded in local wisdom with high strategic value for border community food security. The cultivation of organic adan rice, holding a Geographical Indication (GI) certificate, serves as both a cultural identity and flagship commodity. However, development of this organic agriculture faces significant challenges: geographic isolation, inadequate infrastructure, low product competitiveness, and suboptimal farmer institutional capacity. This study aims to identify the most effective policy strategy for developing Krayan organic agriculture to strengthen sustainable food security in border areas. The research employs a descriptive-analytical approach using USG (Urgency, Seriousness, Growth) for problem prioritization and Expert Judgment-based weighted criteria analysis for policy selection. Results indicate that among three policy alternatives evaluated, the Integrated (Holistic) Approach achieved the highest weighted score of 4.55 out of 5.00. Policy recommendations require cross-ministerial synergy, supported by state budget, regional budget, village funds, international grants, and private investment.